PERSEPSI MASYARAKAT TERHADAP KINERJA PEMERINTAH DALAM RANCANGAN ANGGARAN DANA DESA SAMBIRAMPAK KIDUL KABUPATEN PROBOLINGGO - Dewi, Novita Sari Tri Tungga (Universitas Panca Marga, 2024)
The smallest environment in a government is the Village Government where this village command has duties in the welfare of the community and development of the village. The village fund budget (ADD) is a budget income from the government to make the village independent and improve the community's standard of living. With the Village Fund Allocation (ADD) as an embodiment of Community Welfare and also Village development, this will involve the community in it so that there is no social inequality. This village fund is a budget income from the Indonesian government to solve existing problems such as the economy, development, inadequate facilities. The problem that occurs in Indonesia when managing village funds is that the village fund budget is not used properly by certain officials within the government sphere, so with this we need to use the community's perception of government performance by involving village fund management and also knowing what are their methods of achieving a goal in managing the village fund budget and whether they have used the rules according to the law. The research results show that the community's perception shows and can be concluded that the village fund budget implementation stage implements an Accountable, Participatory and Transparent system and is in accordance with statutory regulation. Keyword : Perception, Performance, ADD